2007
DOI: 10.2116/analsci.23.829
|View full text |Cite
|
Sign up to set email alerts
|

Au Nanorod Arrays Tailored for Surface-Enhanced Raman Spectroscopy

Abstract: IntroductionFor applying local field enhancement arising from local plasmons present in noble metal nanoparticles to biochemical sensors, such as surface-enhanced Raman scattering (SERS) sensors, it is important to control both the shape and the arrangement of the nanoparticles.1 It is well known that wellordered 2D periodic arrays of triangular nanoparticles prepared by nanosphere lithography (NSL) show plasma resonance within a rather narrow wavelength region, and the sharp corners of the triangles result in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 18 publications
1
55
0
Order By: Relevance
“…In the case of serial bideposition, the shadowing area lies alternately in front of and behind the columns, and, accordingly, the intercolumn gaps are widened, and bundles are formed more visibly. 6 Therefore, the degree of anisotropy of the surface morphology is considerably higher than that of a conventional obliquely deposited film.…”
Section: Microstructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of serial bideposition, the shadowing area lies alternately in front of and behind the columns, and, accordingly, the intercolumn gaps are widened, and bundles are formed more visibly. 6 Therefore, the degree of anisotropy of the surface morphology is considerably higher than that of a conventional obliquely deposited film.…”
Section: Microstructuresmentioning
confidence: 99%
“…Several researchers have reported solutions 2,4 for improving the transmittance, which depends on the smaller birefringent, Δn, and, occasionally, on film haze. 1 Several studies have reported that the retardation films prepared by the serial bideposition technique [4][5][6] have nanostructural growth perpendicular to the substrate, and can therefore be used for increasing Δn. Film thickness could decrease at high values of Δn.…”
Section: Introductionmentioning
confidence: 99%
“…Au nanorods were aligned on a SiO 2 template layer (called the "shape control layer") having an anisotropic surface morphology prepared by OAD. 6 The shape control layer of SiO 2 as the template for Au nanorods is prepared by a serial bideposition (SBD) technique. The glass substrate is set obliquely at a deposition angle of about 80 deg.…”
Section: Au Nanorod Arrays For Surface-enhanced Raman Scatteringmentioning
confidence: 99%
“…As a result, the surface of the shape control layer prepared by SBD is corrugated anisotropically. 6,7 On the anisotropic shape control layer, Au is also evaporated obliquely in vacuum. The amount of deposited Au is only around 10 nm thick on average.…”
Section: Au Nanorod Arrays For Surface-enhanced Raman Scatteringmentioning
confidence: 99%
See 1 more Smart Citation